Analisis Uji Beda Kontribusi Ekonomi Ibu Rumah Tangga dari Sektor Jasa Bidang Pertanian di Kecamatan Andowia Kabupaten Konawe Utara - Hermawan, Jojon; Abdullah, Weka Gusmiarty; Rianse, Ilma Sarimustaqiyma (Jurnal Ilmiah Membangun Desa dan Pertanian, 2017)
The study aims to determine the amount of income, income contribution to total household income, and how the difference in income contribution of housewife working in oil palm plantations and working as traders in traditional markets. The research location was done by purposive and sample housewife who work as oil palm plantation as many as 60 people and work as a trader in the traditional market as much as 37 people. Data analysis that was used in this study were income analysis, income contribution, and t-test analysis of difference(t-test). The results showed that the average income of housewife who works as laborers in oil palm plantation IDR 1.038.300, - / month and work in traditional market IDR 1.359.204, - / month. The income contribution of a housewife from working as oil palm plantation workers and those who work as traders in traditional markets was the same, about 30% of total household income. The difference in income contribution of housewife working on oil palm plantations and working in traditional markets to total household income was not different, statistically